Mean Cell Volumes of Neutrophils and Monocytes as Promising Markers of Sepsis in ICU Patients of Sri Ramachandra Medical Centre, Chennai - S, Muthuraj.; Suman. D, Febe Renjitha; B, Sendilkumar.; Cruze, Lawrence D (Journal of Neonatal Surgery, 2025)
Backround: VCS (Volume, Conductivity, and Light Scatter) parameters seem to be promising indicators for the diagnosis of sepsis. This study aimed at assessing the diagnostic significance of VCS parameters for sepsis in ICU patients and at comparing their reliability with that of inflammatory markers. Material & Methods:Patients were divided into 3 groups according to their clinical history and Control (N=60), localized infection (N=40), and systemic infection (N=80).VCS parameters were obtained using a Beckman Coulter LH 780 system. Medical records of sepsis patients are perused by the investigator and Hematological parameters are archived from the laboratory data. Results:The mean volumes of monocytes (MMV), conductivity and light scatter were higher in the sepsis group than in the control groups and localized infection (P=0.000).No difference was noticed in the mean cell volume, conductivity of neutrophils between groups, however the mean cell volume, scatter of neutrophils in sepsis (p=0.016) was lower than in localized infection and control groups (p=023).